Learning strategy and higher order thinking skills of students in accounting studies: correlation and regression analysis - Jamaluddin, Nor Sa'adah; Abdul Kadir, Suhaida; Abdullah, Arnida; Alias, Siti Noormi (Human Resource Management Academic Research Society, 2019)
The mastery of Higher Order Thinking Skills (HOTS) among students is a reflection appropriate learning strategies that students have applied. Therefore, the choice of learning strategies that are relevant to the subjects being studied is seen as contributing to the successful in mastering of HOTS among students. However, does this response also occur in the selection of learning strategies and HOTS’s mastery in Accounting Studies? Hence, this research was conducted with the aim of examining the relationship between HOTS and learning strategies in Accounting Studies. This study is conducted by employing correlation research method on 340 students studying Accounting Studies in Peninsular Malaysia participated in this research through completing a self-administered questionnaire which included the Learning and Study Strategies Inventory (LASSI) and Higher Order Thinking Skills Test. Applying skills, analytical skills, evaluative skills, and creative skills are among the four elements of HOTS tested. The analysis showed that positive significant relationship (r = 0.194) exists between the two variables and the regression equation is an average grade point = 46.442 + 4.349 Learning Strategies. Thus, through correlation and regression analysis, significant regression model between HOTS and Learning Strategies were found.